PROBLEMS WITH CLEAN WATER SOURCES FOR COASTEL COMMUNITIES IN KUALA LANGSA VILLAGE, ACEH PROVINCE - Lubis, Susi Mulianti; Pratiwi, Riska Tia; Farahdina, Inka; Rezeki, Shally (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
Public perception, clean water, PDAM